Археологические исследования ближайшей округи Сугдеи в 2007—2008 гг. - Майко, В.В.; Джанов, А.В.; Фарбей, А.М. (Археологічні дослідження в Україні, 2009)
The results of the excavations of two necropolei in suburbs of Sugdea are published in the paper. Part of the burials of Sudak IX necropolis belongs to the first half of the 15th c. Ground undercut graves with the complicated wooden constructions, belonging to the nomads turning to settled residents, could be dated back to the first half of the 13th c. The burials overlay the dwelling, husbandry, and burial structures of the 8th—9th c. and of the middle of the 14th c. The burials at the necropolis in St. Paraskeva temple testify to the existence of the burial ground before the building of a present church. The earliest tombs are dated to the second half of the 13th c.